Visions and commemoration of the end of the ’problem’ in Morocco during the Primo de Rivera dictatorship - Iglesias Amorín, Alfonso (Hispania Nova, 2021)
It is hard to understand the regime established in Spain in 1923 without bearing in mind the protectorate of Morocco. The dictatorship was partly a consequence of the Annual disaster, and solving the "Morocco problem" was one of its great goals. Having achieved this after the landing of Alhucemas led the regime to turn what was then called "pacification" into a prodigious merit, used to legitimize the dictatorship and its leader. For this reason, the commemoration of the war in Morocco was a key element of Primoriverist propaganda. In this sense, the realization of tributes and the granting of merits to the protagonists stood out, as well as a control of the cultural products through propaganda and censorship, which ensured the adaptation of these to the official discourse of the regime. Precisely the analysis of this biased discourse is of great interest to know the orientation of the regime and the construction of a certain memory of the Moroccan campaigns.